Attack of the 50-foot social justice warrior: the discursive construction of SJW memes as the monstrous feminine. Issue 4 (4th July 2018) - Massanari, Adrienne L.; Chess, Shira
Abstract: This essay considers the origin and meaning of "social justice warrior" (SJW) memes. Despite each term within the phrase suggesting potentially positive connotations, we argue that as deployed within "alt-right" communities, it implies a kind of monstrous feminine: a woman who is unwieldy and out of control. We catalogue and analyze this meme using a visual discourse analysis of texts gathered through Google Images and Reddit. Our findings suggest that the SJW meme is deployed to emphasize opponents as having non-normative, problematic bodies, different brains (ones ruled by emotion rather than logic), and monstrous characteristics. We argue that such discourse is potentially dangerous, but that feminists may have the tools to recreate the SJW as an image of power.